Supranational institutions and peacebuilding in Africa
1 online resource.
Keywords: "This book analyses the role of the African Union and regional economic communities in contributing to peacebuilding in Africa. Big and small conflicts rage across the African continent, and this book argues that the African Union and the five regional economic communities have the potential to greatly contribute to peace and peacebuilding In Africa. Looking across the African Union and the five regional economic communities (the AMU, ECCAS, ECOWAS, IGAD, and SADC), the book considers in detail the organizations' programmes, engagement, endeavours, success and failure of activities of peacebuilding in their respective regions. Overall, the book argues that an institutionalised and formalised relationship between the African Union and the regional economic communities would not only be decisive for the prospects for peace in the region but would also serve to strengthen the continent's role on the global stage through asserting its agency, owning its agenda, and designing its own solutions and mechanisms for addressing problems. Drawing together an international team of prominent experts, this book will be of interest to researchers, policymakers, NGOs, activists, and regional and international actors working on African politics, security, governance, and economics"--